2022
DOI: 10.1002/pbc.30166
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic CD34+ selected hematopoietic stem cell boost following CAR T‐cell therapy in a patient with prolonged cytopenia and active infection

Abstract: Hematological toxicity (hematotoxicity) leading to peripheral cytopenias is a common long‐term adverse effect following the use of CD19‐chimeric antigen receptor (CD19‐CAR) T‐cell therapies. However, management remains unclear for patients whose cytopenias persist beyond 1 month after CAR T‐cell infusion. We present the case of a 21‐year old who received CD19‐CAR T‐cell therapy for relapse following a haploidentical transplant. He developed hematotoxicity and consequently multiple life‐threatening infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…CD8+ T‐cells and CD56+ natural killer (NK) cells fully recovered in all patients by 1 year, while reconstitution of CD4+ T cells was delayed, with normalization in only 67% of patients at 1 year. Similarly, in 39 CAR‐T recipients with R/R, the absolute counts of CD4+, CD8+, and CD16/56+ lymphocytes decreased significantly after lymphodepleting chemotherapy: while CD8+ and CD16/CD56+ cell counts rapidly recovered in all patients at a median time of 21 days, 7–10,12–15,17,21,22,24–64,66–92 a slower recovery was observed for CD4+, which recovered within 60 days in only 5 (23.81%) of patients 71 …”
Section: Immune Reconstitutionmentioning
confidence: 90%
See 2 more Smart Citations
“…CD8+ T‐cells and CD56+ natural killer (NK) cells fully recovered in all patients by 1 year, while reconstitution of CD4+ T cells was delayed, with normalization in only 67% of patients at 1 year. Similarly, in 39 CAR‐T recipients with R/R, the absolute counts of CD4+, CD8+, and CD16/56+ lymphocytes decreased significantly after lymphodepleting chemotherapy: while CD8+ and CD16/CD56+ cell counts rapidly recovered in all patients at a median time of 21 days, 7–10,12–15,17,21,22,24–64,66–92 a slower recovery was observed for CD4+, which recovered within 60 days in only 5 (23.81%) of patients 71 …”
Section: Immune Reconstitutionmentioning
confidence: 90%
“…If CAR-T cells were administered after a previous allogeneic HSCT, donor-derived CD34+ boost in patients experiencing persistent grade ≥ 3 cytopenias has also been reported, with no GVHD occurrence. 21,91,92 When sequential treatment with tandem infusion of CAR-T and autologous or allogeneic HSCT was performed inside clinical trials, it was observed that CAR-T did not impact hematopoietic recovery or GVHD after transplants. 93,94 In a real-life survey, autologous stem cell boosts, when available, were the preferred option for the rescue of persistent neutropenia in 63% of centers, while it was considered a therapeutic option for persisting thrombocytopenia refractory to TPO-RA by 43% of experts.…”
Section: Hematopoietic Stem Cell Boostmentioning
confidence: 99%
See 1 more Smart Citation
“…In two case reports, auto‐HSCB reversed CAR‐T‐cell‐mediated prolonged pancytopenia in lymphoma and multiple myeloma patients 81,82 . Similarly, allo‐HSCB improved the prognosis of two B‐ALL patients with prolonged cytopenia and infection following CAR‐T‐cell therapy 83,84 . In addition to case reports, a multicentre study reported results for 31 patients receiving HSCB (auto, n = 30; allo, n = 1) for sustained severe and moderate neutropenia.…”
Section: Consideration For Treatment Of Prolonged Haematologic Toxicitymentioning
confidence: 99%
“… 81 , 82 Similarly, allo‐HSCB improved the prognosis of two B‐ALL patients with prolonged cytopenia and infection following CAR‐T‐cell therapy. 83 , 84 In addition to case reports, a multicentre study reported results for 31 patients receiving HSCB (auto, n = 30; allo, n = 1) for sustained severe and moderate neutropenia. A total of 84% (26/31) of patients achieved neutrophil recovery or improvement.…”
Section: Consideration For Treatment Of Prolonged Haematologic Toxicitymentioning
confidence: 99%